Orientasi dan Strategi Bertahan Persaingan Kewirausahaan Perempuan pada UMKM - Eka Dewintara; St. Aminah; Syahriyah Semaun; Muliati; Andi Bahri (AL-MAIYYAH : Media Transformasi Gender dalam Paradigma Sosial Keagamaan, 2024)
This research discusses entrepreneurial orientation and survival strategies among female entrepreneurs in the city of Parepare. This research is a qualitative research. The main problem in this research; 1) What is the entrepreneurial orientation of female entrepreneurs in facing MSME competition in Parepare city?, 2) What is the survival strategy of female entrepreneurs in facing MSME competition in Parepare city?, 3) What is the sharia economic perspective of female entrepreneurs in Parepare city in facing MSME competition? ?. Meanwhile, the method used in this research is a qualitative descriptive research method. It was found that female entrepreneurs in the city of Parepare have motivations for entrepreneurship, namely wanting to help the family economy, hobbies, and dreams of owning a business. With the strategy that is carried out so that the business continues to run as desired, namely carrying out regular evaluations (monthly and weekly), seeking knowledge related to the business being undertaken so that the business continues to develop and progress, determining target markets that suit the business, carrying out planning, and provide promotions or discounts to consumers. And it is in line with or in accordance with sharia economic principles. Where the sharia economic principles used are monotheism, justice and balance, free will and responsibility.